RNAi turns 25:contributions and challenges in insect science - Palli, Subba Reddy (Frontiers in Insect Science, 2023)
Since its discovery in 1998, RNA interference (RNAi), a Nobel prize-winning technology, made significant contributions to advances in biology because of its ability to mediate the knockdown of specific target genes. RNAi applications in medicine and agriculture have been explored with mixed success. The past 25 years of research on RNAi resulted in advances in our understanding of the mechanisms of its action, target specificity, and differential efficiency among animals and plants. RNAi played a major role in advances in insect biology. Did RNAi technology did not fully meet insect pest and disease vector management expectations? This review will discuss recent advances in the mechanisms of RNAi and its contributions to insect science, and remaining challenges, including delivery to the target site, differential efficiency, potential resistance development and possible solutions for the widespread use of this technology in insect management.